Seismic Activity of Volcano-tectonic Earthquakes at Guntur Volcano, West Java, Indonesia During the Period from 1991 to 2005 - Nurlia Sadikin; Masato Iguchi; Gede Suantika; Muhamad Hendrasto (Indonesian Journal of Physics, 2007)
Volcano-tectonic earthquakes at Guntur volcano were analyzed. The hypocenters are distributed in 3 regions; around the summit area from Masigit volcano to Guntur volcano at depths <2km, Gandapura caldera at depths <3km and around Kamojang geothermal field at depths of 2-8km. The focal mechanisms are characterized by normal and reverse faults in the summit area and normal fault in Gandapura. The mechanism is dominated by strike-slip fault type in Kamojang. Although eruptivity of Guntur volcano has been dormant since 1847, VT earthquakes beneath the summit area and Gandapura may be related with intermittent intrusion of magma, considering focal mechanism of VT earthquakes and uplift of the ground around the summit area and Gandapura. However, the seismic energy release stayed at lower level than threshold preceding magmatic eruption.